2020
DOI: 10.21203/rs.3.rs-44950/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessment of sodium thiosulfate neutralizing effect on micro-hardness of dentin treated with sodium hypochlorite

Abstract: Background: This study aims to evaluate the ability of sodium thiosulfate (STS) to neutralize the adverse effect of sodium hypochlorite (NaOCl) on dentin micro-hardness.Methods: Fifty single-rooted teeth were longitudinally sectioned. The samples divided into a control and four sample groups (n = 20). All the samples were immersed in different solutions as follows, Control: Normal saline for 15 min, G1and G2: 2.5% NaOCl for 15 min, G3: 2.5% NaOCl for 15 min, followed by 5% STS for 10 min, G4: Normal saline for… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…In contrast, no coloured precipitate formation was visualised in the group in which sodium thiosulphate was used an intermediate irrigant. The absence of this coloured precipitate may be attributed to the neutralising action of sodium thiosulphate, which is in line with several previous studies that have shown the impact of sodium thiosulphate neutralising NaOCl (22,24,27).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In contrast, no coloured precipitate formation was visualised in the group in which sodium thiosulphate was used an intermediate irrigant. The absence of this coloured precipitate may be attributed to the neutralising action of sodium thiosulphate, which is in line with several previous studies that have shown the impact of sodium thiosulphate neutralising NaOCl (22,24,27).…”
Section: Discussionsupporting
confidence: 91%
“…It is well known that the presence of NaOCl remnants inside the root canals during irrigation with CHX can generate a brown-coloured precipitate, for which one of its main by-products is para-chloroaniline (23). To avoid its formation, several intermediate irrigation protocols, including the use of sodium thiosulphate, have been suggested to neutralise residual NaOCl before the use of CHX (18,24). In this regard, the aim of this study was to evaluate the efficacy of sodium thiosulphate as an intermediate irrigant between the use of NaOCl and CHX to avoid the formation of the brown-coloured precipitate.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, irrigation was used (2ml of 2.6% NaOCl for 1 min), with rotary mechanical preparation of root canals, between each file increasing permeability of the chelating agent to the radicular dentin. This has reduced bacterial count, dissolved collagen, and caused oxidation of the organic portion of radicular dentin (15) . Hence, it was limited to 1 minute as prolonged usage of NaOCl can affect dentinal tissue.…”
Section: Discussionmentioning
confidence: 99%